THE USE OF MODERN TEACHING METHODS IN EDITOR EDUCATION IN UKRAINE - Svitlana Fiialka; Hanna Onkovych; Oksana Baliun (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
Modern editor education in Ukraine is traditionally based on learning and reproducing of theoretical knowledge and doesn't account for all possible directions of a graduates` professional career. The author analyses the requirements of the labour market to the competences of the graduates of editing specialities, proposes and justifies the necessity of using the methods of teaching in which the knowledge is acquired in the context of professional activity. Four main skills of a modern editor which should be formed during the learning process are singled out, namely: 1) working with information; 2) interaction with people; 3) operation in a narrow time frame; 4) using the existing experience to acquire new knowledge, solve new tasks under new conditions, unusual situations. So-called active learning, associated with the involvement of participants of learning process into different kinds of activities, is the most effective to form the above mentioned skills. The research proves the efficiency of such organizational forms and methods of learning activities as round tables, group discussions, conferences, case study, editorial analysis, modeling of editorial and publishing processes, interviews, teamwork, analysis of publications, mini-lectures, video trainings, presentations, simulation games, analysis of problematic cases and atypical errors etc. These methods allow students to develop flexibility of thought, adaptation to real work situations, initiative, autonomy in decision-making and at the same time the ability to work in a team, creative approach to problem-solving. The result of using these teaching methods with the elements of competition, autonomy at the lesson, peer evaluation is the formation of professional and personal qualities, understanding the need for ongoing professional self-education. All these methods of learning activities of students got approval in the questionnaires and group discussions.